Social and health system barriers: Investigating Circumstances of Mortality Categories (COMCATs) for deceased patients with T2DM in the sub-national Saudi Arabia register - Alyazidi, Faleh; Shakely, Deler; Alyazidi, Fawaz; Alnasser, Lubna A.; Petzold, Max; Hussain-Alkhateeb, Laith (PloS one, 2024)
Health policy debates rely on reliable and timely information on major causes of mortality and their associated attributors, especially to overcome the traditional public health focus restricted to the biomedical cause of death (COD). This study explores relevant social and health system circumstantial barriers to accessing healthcare services among deceased patients with Type 2 Diabetes Mellitus (T2DM) in Saudi Arabia. A total of 302 verbal autopsy (VA) interviews were conducted with relatives or caregivers of the deceased who died between 2018 and 2021, based on T2DM medical records from Alnoor Specialist Hospital in the Western Province, Saudi Arabia. The Bayesian-based InterVA-5 algorithm was employed as a validated source to determine the probable COD and Circumstances Of Mortality Categories (COMCATs) for each case. COMCATs stand for predetermined categories of multiple social and healthcare system circumstances that contribute to an individual’s death. The likelihoods of COD and COMCATs derived from InterVA-5 software were computed independently to generate the ‘cause-specific mortality fractions’ (CSMFs) of the COD and COMCATs. The CSMFs for the seven COMCATs categories were then ranked based on their derived probabilities for the corresponding COMCATs across all major COD categories. The top CODs were circulatory diseases (35.8%), stroke (16.6%), and diabetes mellitus (14.3%). The probabilities of COMCATs indicated that most deaths were attributed to ‘inevitable’ causes (e.g., terminal illness), followed by ‘recognition’ (inability to recognize the severity of illness) and ‘traditions’ (local attitudes deterring patients from seeking medical services on time). Addressing ‘recognition’ and ‘traditions’ barriers could reduce mortality rates and improve access to healthcare, helping the Saudi health system accelerate the progress towards the systematic measurement of key universal health coverage indicators. The study emphasizes the need for a robust and standardized VA method within routine medical services to address factors influencing healthcare access towards improved health outcomes.